Chorionic villi carbohydrate determinants study in early pregnancy loss. - Zastavnyy, I.; Yashchenko, A.; Tkach, I. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. There are two types of pregnancy miscarriage – the sporadic (SM) and recurrent (RM). The frequency of RM among reproductive age women reaches 2-5%. There are many reasons of RM and in approximately 50% of all cases they are defined as “immune infertility”, the mechanisms of which are not completely known. Objectives. The purpose of the study was to investigate morphological changes and glycome features of the structural components of human embryos chorionic villi (CV), died out as a result of the first trimester miscarriage. Methods. Histological material included 28 4-13-week human embryos CV tissue samples, obtained after SM, RM and 20 control group CV samples. They were stained with hematoxylin and eosin. Lectin peroxidase technique was applied, using 8 lectins (Con-A, HPA, LABA, SBA, SNA, CNFA (CNL), AIA, VAA). Results. Destructive changes were observed in RM chorionic villi samples. With the help of lectin peroxidase technique, we have identified one most active lectin – CNFA (CNL). Conclusions. We admit that one of the mechanisms of a regular early pregnancy loss can be a reduced expression of LacdiNAc - carbohydrates in some chorionic villi structural components, and as a result – unmasking an embryo against negative external factors, including such of immune nature.